Analysis of Factors Affecting Customer Loyalty with Customer Satisfaction as an Intervening Variable on Indomie Products in Superindo Bekasi Regency - E.H.J. FoEh, John; Priyo, Dimas (Dinasti International Journal of Management Science, 2024)
This study set out to ascertain, using customer satisfaction as an intervening variable, the impact of the independent variables—such as brand image, product quality, and promotion—on the dependent variable of consumer loyalty. This study was carried out in the Bekasi Regency's Superindo. This study employed a quantitative methodology. Primary data obtained through a questionnaire were used in this investigation. The Accidental Sampling technique was the sampling strategy employed in this investigation. The population under investigation comprises all Superindo clients. 221 respondents served as samples for this study, which was determined by using the table that Isaac and Michael created to determine the number of samples. The analysis process makes use of path analysis, multiple linear regression analysis, and descriptive quantitative analysis. The data was processed using SPSS version 25, a programme for data analysis. The results of the study indicate that brand image, product quality, and promotion all positively and significantly affect consumer satisfaction, either simultaneously or in part. In Superindo Bekasi Regency, these factors also positively and significantly affect customer loyalty to Indomie products.